2014
DOI: 10.2527/jas.2013-6598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow rate and gas mixture on the welfare of weaned and neonate pigs during gas euthanasia1

Abstract: The objectives of this study were to assess efficacy and welfare implications of gas euthanasia when applied to weaned and neonate pigs. Parameters associated with welfare, which were measured before loss of consciousness, included open-mouth breathing, ataxia, righting response, and escape attempts. Two age groups (weaned and neonate) were assessed in 9 gas treatments arranged in a 2 × 4 factorial design, with 2 gas types (CO 2 = 100% CO 2 and 50:50 = 50:50 CO 2 :argon) and 4 flow rates (box volume exchange/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In terms of the visual esthetics of technique, the convulsive stage, arguably the most disturbing period to an unfamiliar audience, was actually shorter for weaned pigs than the durations reported for neonates (Casey-Trott et al, 2013). Conversely, Sadler et al (2014) observed that neonates succumbed faster than weaned pigs when using inhalant euthanasia techniques with carbon dioxide and argon gases. This contrasting result may be related to the differences in the mode of action between physical and gaseous euthanasia techniques, with physical methods causing direct destruction of neuronal tissues and gaseous methods causing hypoxic conditions in the brain leading to tissue death (AVMA, 2013).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In terms of the visual esthetics of technique, the convulsive stage, arguably the most disturbing period to an unfamiliar audience, was actually shorter for weaned pigs than the durations reported for neonates (Casey-Trott et al, 2013). Conversely, Sadler et al (2014) observed that neonates succumbed faster than weaned pigs when using inhalant euthanasia techniques with carbon dioxide and argon gases. This contrasting result may be related to the differences in the mode of action between physical and gaseous euthanasia techniques, with physical methods causing direct destruction of neuronal tissues and gaseous methods causing hypoxic conditions in the brain leading to tissue death (AVMA, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…These grand mal convulsive movements are involuntary neuromuscular responses indicative of epileptiform brain activity following severe concussion (Shaw, 2002) and during electrical stunning in pigs (McKinstry and Anil, 2004). Varying degrees of these convulsive movements have been reported following application of all available euthanasia techniques for pigs including BFT and NPCB (Chevillon et al, 2004;Widowski et al, 2008;Woods, 2012) and CO 2 (Raj and Gregory, 1996;Sutherland, 2010;Sadler et al, 2014). The convulsive period was similar to the 1 to 1.5 min typically seen with BFT (Chevillon et al, 2004;Widowski et al, 2008) and shorter than other NPCB devices falling within the range or 1 to 4 min reported by Woods (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several gases are currently used to euthanise, stun or kill animals, including CO 2 and the inert gases, argon (Ar) and nitrogen [ 10 , 11 , 12 , 13 ]. Gaseous methods are routinely used for laboratory rodents, with CO 2 being the most commonly used agent because it is heavier than air and thus containable, cheap to obtain and relatively safe for human operators [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elimination behavior in kids was low across all days, and did not increase or decrease consistently. Escape attempts are generally observed when an animal is in an environment that is perceived as threatening, and escape attempts are exhibited in pigs and rodents during gas exposure (Niel and Weary, 2006, Llonch et al, 2012, Chojnacki et al, 2014, Sadler et al, 2014b, Barnard et al, 2015. The lack of escape attempts during gas treatments may be an indicator of a lack of fear in response to CO2, but it may also be associated with the ataxia that accompanies CO2 exposure.…”
Section: Fear Behaviorsmentioning
confidence: 99%
“…CO2/minute box volume replacement rate (Gerritzen et al, 2004, Sadler et al, 2014a. While this induction time is relatively fast, there is still the potential for distress and pain during the animals' conscious period.…”
Section: Introductionmentioning
confidence: 99%